Sex Difference in the Association Between Eating Away From Home and the Risk of High Serum Uric Acid in South China - Chen, Shao-wei; Wang, Ping; Ji, Gui-yuan; Jiang, Qi; Hong, Xiao-min; Ma, Wen-jun; Huang, Rui; Chen, Zi-hui; Peng, Jie-wen (Frontiers in Nutrition, 2021)
Background: The prevalence of high serum uric acid is increasingly rising in recent years, and diet behavior is perceived to be associated with it. This study aimed to explore the relationship between eating away from home (EAFH) and the risk of high serum uric acid in adults in South China. Methods: The data utilized in this study were from Guangdong Nutrition and Health Survey (NHS) 2015. Serum uric acid concentration was detected. EAFH in the past week was investigated. We defined EAFH as food consumption away from home. Dietary data were collected by 24-h recalls on 3 consecutive days. A generalized linear mixed-effects model was applied to compute the odds ratio (OR) and its corresponding 95% CI. Results: A total of 3,489 individuals were included in this study. A 1.27-fold OR (95% CI: 1.05–1.52, P = 0.012) of high serum uric acid was identified in adults with EAFH in comparison with those without EAFH. With respect to men, a 1.66-fold OR (95% CI: 1.3–2.1, P < 0.001) of high serum uric acid was observed. We also observed that men with EAFH had higher intakes of red meat, poultry, vegetable, carbohydrate, protein, fat, and total energy, while a lower grain intake than those without EAFH. However, there was a lack of significant association between EAFH and the odds ratio of high serum uric acid in women. Women with EAFH did not have higher consumptions of red meat, vegetable, fish, fat, and water than those without EAFH. Conclusions: This study found that EAFH was associated with an increased odds ratio of high serum uric acid in men, but not in women.